Ceria Zirconia Mixed Oxides Prepared by Hydrothermal Templating Method for the Oxidation of Ethyl Benzene - Cimi A. Daniel; S. Sugunan (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2013)
CeO2–ZrO2 oxides were prepared by the surfactant-templated method using cetyl trimethyl ammonium bromide (CTAB) as template. These were characterized by XRD, FT-IR, TEM, SEM, BET and TPD-CO2. The XRD data showed that as prepared CeO2-ZrO2 powder particles have single phase cubic fluorite structure. HRTEM shows mesoscopic ordering. Average particle size is 12-13 nm as calculated from particle histogram. The nitrogen adsorption/desorption isotherm were classified to be type IV isotherm, typical of mesoporous material. The presence of uni-modal mesopores are confirmed by the pore size distribution which shows pore distribution at around 60 A°. The catalytic activities of the prepared material were tested in liquid phase oxidation of ethylbenzene with tert-butyl hydroperoxide (TBHP) as an oxidant. Ceria zirconia catalyst modified with chromium was active for ethylbenzene conversion (65.3%) with 77% selectivity towards acetophenone. © 2013 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)